1989
DOI: 10.1002/j.2050-0416.1989.tb04638.x
|View full text |Cite
|
Sign up to set email alerts
|

Starch Degradation in Endosperms of Developing Barley Kernels*

Abstract: Shortly after anthesis, empty endosperm cells adjacent to the embryo were crushed between the developing embryo and endosperm tissues to form the crushed cell layer. Starch granules in cells adjacent to this layer were hydrolysed and the empty cells were added to the crushed layer. In this way, the crushed layer increased in thickness throughout kernel development. a-Amylase 2 was detected in the crushed cell layer region of barley endosperms during the period that starch granule hydrolysis was occurring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The disappearance of starch granules in this tissue strongly coincides with AMY enzyme activity (MacGregor and Dushnicky, 1989a). AMY enzyme activity was also detected in the embryo-surrounding region of the endosperm (MacGregor and Dushnicky, 1989b). BAM enzyme activity was measured in the barley endosperm at later developmental stages (Beck and Ziegler, 1989).…”
mentioning
confidence: 63%
“…The disappearance of starch granules in this tissue strongly coincides with AMY enzyme activity (MacGregor and Dushnicky, 1989a). AMY enzyme activity was also detected in the embryo-surrounding region of the endosperm (MacGregor and Dushnicky, 1989b). BAM enzyme activity was measured in the barley endosperm at later developmental stages (Beck and Ziegler, 1989).…”
mentioning
confidence: 63%
“…The relationship between enzymatic activity and breadmaking quality It has been reported that the increases of ␣-amylase and endo-protease activities in wheat are related to the degradation of flour (Jones & Wrobel, 1993;MacGregor & Matsuo, 1972;MacGregor & Dushnicky, 1989;Prestone & Kruger, 1979). However, the relationship between the enzymatic activities and the breadmaking quality of wheat during germination is not always clear.…”
Section: Germination Effect On Breadmaking Qualitymentioning
confidence: 99%
“…and is unsuitable for industrial processing. Many studies on germination damage in wheat deal with starch degradation, i.e., MV of Amylograph, Falling number, ␣-amylase activity and the quality of bread (MacGregor & Matsuo, 1972; Meredith & Pomernz, 1985;MacGregor & Dushnicky, 1989). However, the deterioration of breadmaking quality in flour that has been damaged during sprouting cannot always be explained by low MV values (Yamauchi et al, 1998;Sato et al, 1999).…”
mentioning
confidence: 99%
“…The flour of the grains damaged by pre-harvest sprouting has a maximum viscosity (MV) in amylography below 300 BU and is unsuitable for industrial processing. Many studies have shown that endosperm starch degraded by a-amylase activity may adversely affect the quality of flour for noodles (Yasunaga et al, 1963;MacGregor and Matsuo, 1972;MacGregor and Dushnicky, 1989;Salomonsson et al, 1989;Matsuzaki and Toyoda, 1996). The degradation of endosperm protein caused by endoprotease may greatly contribute to the deterioration in bread-making quality (Preston et al, 1978;Lukow et al, 1984;Janssen et al, 1996;Weegels et al, 1996).…”
mentioning
confidence: 99%